Evaluation the prevalence of moderate chronic periodontitis among smokers and non- smokers in Aljouf province , Kingdom Of Saudi Arabia - Hashem, Ahmed Shawkat; Ismail, Hesham Shokry; Patil, Santosh R; Alam, Mohammad Khursheed (International Journal of Human and Health Sciences (IJHHS), 2018)
Background: Due to limited data about the prevalence of the moderate chronic periodontitis among smokers and non- smokers in Saudi population this study was conducted. Methods: For each participant, full mouth periodontal examination was performed and recorded on a special examination form by one of the 3 examiners. These data included probing depth (PD), clinical attachment level (CAL). The Data was collected and entered into the personal computer. Statistical analysis was done using Statistical Package for Social Sciences (SPSS/version 21) software. Number and percent of each category were calculated, for categorized parameters, chi square test was used. The level of significant was 0.05. Results: On comparison the prevalence of moderate chronic periodontitis among the smoker and non- smoker groups, chi square test was 9.114, with ( p< 0.05) which is statistically significant, while on comparison the age between the two groups, it was found that there was no significant relation between the age and the different grade of chronic periodontitis. Conclusion: Moderate Chronic Periodontitis is more prevalent among smokers in Aljouf province, Kingdom of Saudi Arabia. International Journal of Human and Health Sciences Vol. 02 No. 03 July’18. Page : 145-148